Comparison of curriculum implementation between public and private schools based on Adiwiyata - Mohamad Joko Susilo; Junanah Junanah; M Hajar Dewantoro (Intelektual Pustaka Media Utama, 2021)
The curriculum is the heart of education, whose job determines the life or death of a school. This study aimed to compare the implementation of Adiwiyata school curriculum between public and private school in junior high schools, especially in Bantul Regency, Yogyakarta, Indonesia. Data collection techniques by means of literature studies. Data analysis techniques were carried out with qualitative comparative analysis. The results showed that: public and private schools in junior high schools in Bantul Regency, had fulfilled the four main components of the Adiwiyata curriculum, in terms of objectives, content, methods, and evaluation. The implementation of Adiwiyata curriculum in each public and private school varies according to the characteristics and potential of each school.